ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI RETURN SAHAM DI MASA PANDEMI COVID-19 PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Nadya Danah Sabbita; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2022)
Stock Return is the return or yield on shares that have been invested by investors, can be in the form of dividends or capital gains.  Stock returns are used as a reference and consideration for investors before making investment decisions.  Many factors affect stock returns, one of which is financial ratios that can be seen through liquidity ratios, solvency ratios, and profitability ratios.  Analysis of the factors that affect stock returns during the Covid-19 pandemic in banking companies listed on the IDX.  The purpose of this study was to determine the effect of liquidity ratios, solvency and profitability on stock returns of banking companies during the COVID-19 pandemic, either simultaneously or partially.  The type of method used in this research is correlative research with a quantitative approach.  The data used are secondary data with a research period of 1 year.  The population in this study are banking companies listed on the IDX.  The sampling technique used purposive sampling method and obtained 19 companies with a total sample of 76 using quarterly financial statements.  Data analysis used multiple linear regression analysis, while data processing used IBM SPSS 22. The results of this study indicate that the liquidity ratio as measured by the cash ratio has a significant negative effect, and the solvency ratio as measured by the debt to equity ratio has no effect on stock returns, while  profitability ratios as measured by return on assets have a significant effect on stock returns.Keywords : stock return, liquidity ratios, solvency ratios, profitability ratios